PENGUJIAN NILAI KEKESATAN PERMUKAAN JALAN PADA JALAN UTAMA AHMAD YANI 1 PONTIANAK - Novianto, Verry; Widodo, Slamet; Sulandari, Eti (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2018)
Road is an important vehicle in transportation.Traffic density in the city of Pontianak increased due to rapid population growth, so the road affects the safety and comfort of the riders. Good road planning has an effect on the level of road performance, where the road surface has a rigid value. The purpose of the researcher is to find the influence of temperature on road surface roughness and to know the value of road surface crawl on the surrounding area of red light of UNTAN roundabout and before the red light. In this research, the value of aggravation using BPT tool (Bristish Pendulum Tester). Research location is done on Ahmad Yani road 1 Pontianak roundabout UNTAN Pontianak. The time specified in the data collection is morning, noon and afternoon with sunny weather conditions. From the survey results show that the temperature affect the value of road surface crunchiness, if the low temperature of high road surface aggravation value and vice versa if the high temperature then the value of road surface crashes decreased. On the left side (motorcycle) station 0 + 150 in the morning with a surface temperature of 250c obtained BPN 44.8 value, during the day the surface temperature increased to 420c with the value of BPN 30, in the afternoon the temperature dropped back to 300c showed the value of BPN 39 , 6. Keywords: BPT (British Pendulum Tester), BPN (British Pendulum Number)